THE EFFECTIVENESS OF PHARMACOLOGICAL, DIETARY, PSYCHOLOGICAL AND NOVEL TREATMENTS IN IRRITABLE BOWEL SYNDROME - Dominika Gieroba; Anna Kamieniak; Weronika Perczyńska; Gabriela Kapłon; Julia Szczotka; Gabriela Szpila; Artur Tumiński; Marianna Chmiel; Aleksandra Sokół; Remigiusz Flakus; Żaneta Kania; Karolina Glajcar (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: Irritable bowel syndrome (IBS) is a functional disorder of the gastrointestinal tract with a complex pathogenesis in which the brain-gut axis is disrupted. Due to the multifactorial basis of the disorder, it is very important to combine pharmacological and psychological treatment with dietary treatment to alleviate patients’ symptoms. The purpose of this dissertation was to present the effectiveness of pharmacological, dietary, psychological and novel treatments currently at research level in patients with irritable bowel syndrome. Method: In order to evaluate the effectiveness of various therapies in IBS, a systematic review was conducted. It covers articles from years 2020 - 2024, that were published in PubMed, MDPI, and Sage Journals databases. Key Findings: The treatment of irritable bowel syndrome requires a combination of different therapies to achieve an effective therapeutic effect. There is no specific form of treatment to cure IBS. Conclusions: Currently it is only possible to alleviate the discomfort and improve the quality of life by combining the various methods available. The method that seems to be the most effective is a combination of pharmacological, dietary and psychological treatment. Pharmacological therapy makes it possible to alleviate pain, constipation or diarrhea. The introduction of the FODMAP diet eliminates factors that adversely affect the intestinal microbiota, and psychotherapy, combined with pharmacological treatment of depression and anxiety, alters thinking and synthesizes hormones that affect the gut-brain axis. Alternative treatments are currently being researched, but it will take time and further research before these methods can be incorporated into standard therapy.